2005
DOI: 10.1136/tc.2004.008581
|View full text |Cite
|
Sign up to set email alerts
|

Environmental tobacco smoke exposure in public places of European cities

Abstract: Background: Exposure to environmental tobacco smoke (ETS) has important public health implications. The results of the first European multi-centre study that measured ETS exposure in a range of public places (transport, educational settings, and leisure facilities such as bars and restaurants) are presented. Method: Nicotine vapour phase was measured using ETS passive samplers containing a filter treated with sodium bisulfate. Results: Bars and discos are the places with the highest concentrations of nicotine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
63
1
6

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 26 publications
5
63
1
6
Order By: Relevance
“…Earlier studies reported high concentrations of nicotine, fine and ultrafine particulates in the indoor air of hospitality establishments [4][5][6], a correlation between air nicotine and active particle surface [7], with relatively highest exposures in Vienna in international comparison [4], but a systematic exposure assessment in comparison with outdoor concentrations over several months was lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies reported high concentrations of nicotine, fine and ultrafine particulates in the indoor air of hospitality establishments [4][5][6], a correlation between air nicotine and active particle surface [7], with relatively highest exposures in Vienna in international comparison [4], but a systematic exposure assessment in comparison with outdoor concentrations over several months was lacking.…”
Section: Introductionmentioning
confidence: 99%
“…An exposure study in seven European cities demonstrated the highest nicotine concentrations in bars and discotheques compared to other public places such as train stations or universities (Nebot et al, 2005). Pubs and discotheques are essential exposure sites for adolescents and young adults.…”
Section: Introductionmentioning
confidence: 99%
“…It was not possible to survey more locations for operational reasons. However, this distribution of samples provided a good estimate of SHS levels in a previous study [5], and prevents an excessive variety of locations, which would make comparisons by location across countries unfeasible. Finally, there was a failure to obtain outdoor measurements for comparison with in-hospital measurements, although, given the low levels obtained indoors, the comparison group would have been almost useless.…”
Section: Discussionmentioning
confidence: 99%
“…A pioneering study that measured airborne nicotine concentrations in 22 hospitals in seven European cities (Vienna (Austria), Paris (France), Athens (Greece), Florence (Italy), Porto (Portugal), Barcelona (Spain) and Ö rebro (Sweden)) during 2001-2002 showed low but detectable SHS exposure in hospitals [5,18,19]. Similar surveys conducted in 11 Latin American countries and China, including one hospital in each country between 2002 and 2006, also showed low but quantifiable nicotine concentrations [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation